A Barrel‐Shaped Metal–Organic Blue‐Box Analogue with Photo‐/Redox‐Switchable Behavior. Issue 69 (28th October 2020) - Brunet, Gabriel; Suturina, Elizaveta A.; George, Guillaume P. C.; Ovens, Jeffrey S.; Richardson, Paul; Bucher, Christophe; Murugesu, Muralee
Abstract: Donor–acceptor interactions are ubiquitous in the design and understanding of host–guest complexes. Despite their non‐covalent nature, they can readily dictate the self‐assembly of complex architectures. Here, a photo‐/redox‐switchable metal–organic nanocapsule is presented, which was assembled by using lanthanide ions and viologen building blocks, by relying on such donor–acceptor interactions. The potential of this unique barrel‐shaped structure is highlighted for the encapsulation of suitable electron donors, akin to the well‐investigated "blue‐box" macrocycles. The light‐triggered reduction of the viologen units has been investigated by single‐crystal‐to‐single‐crystal X‐ray diffraction experiments, complemented by magnetic, optical, and solid‐state electrochemical characterizations. Density functional theory (DFT) calculations were employed to suggest the most likely electron donor in the light‐triggered reduction of the viologen‐based ligand. Abstract : Lock, stock, and blue‐box‐like barrel : A unique self‐assembled metal–organic nanobarrel is achieved by using electron‐deficient viologen‐based linkers and lanthanide ions. The resulting capsule encloses chloride anions and exhibits photo‐/redox‐responsive behavior, enabled by nearby electron donors.